Green Marketing Strategy as an Effort of MSMEs to Enter the International Market: (Study on MSMEs in Laweyan Batik Village, Surakarta, Central Java) - Hariani, Danarti (Universitas Mohammad Husni Thamrin, 2025)
This study aims to be able to formulate the right green marketing strategy in the efforts of Laweyan batik UMKM, Surakarta, Central Java. This research method uses a qualitative descriptive approach in the form of a literature review. The data used are secondary data obtained from literature, journals, scientific works, BPS reports and several survey institutions and the latest data related to the research objectives. While data collection is the methods used to collect data in research in the form of literature studies and documentation observations to observe the potential and development of the Laweyan Batik industry, the application of the green marketing concept to Laweyan Batik UMKM and various supporting data and documentation through internet media. The results of the study indicate that in the development of Laweyan Batik UMKM with a green marketing strategy approach in an effort to enter the international market, there are various problems including: the cost of environmentally friendly batik products is relatively high, Laweyan craftsmen's awareness of environmentally friendly products is still limited, production waste processing technology is not optimal, minimal knowledge and experience of UMKM actors to enter the international market, suboptimal supply chain distribution, and limited market reach to local networks so that in development it requires a green marketing concept to overcome these problems. The development strategy of Laweyan Batik UMKM with a green marketing approach requires constructive efforts through the development of green products, green distribution, green price, green people and green promotion so that the green marketing strategy by Laweyan Batik UMKM in an effort to enter the international market does not only focus on the product marketing aspect, but also covers the entire value chain from raw materials to distribution. Thus, this strategy can increase the competitiveness of Laweyan batik products while supporting global environmental sustainability.